Methods of determination of wetting in highly dispersed systems - Gladkikh, N.T.; Chizhik, S.P.; Larin, V.I.; Grigoryeva, L.K.; Dukarov, S.V. (Gordon and Breach Science Publishers S.A., 1987)
Procedures are described for studying the wetting of solid substrates by island vacuum condensates. The proposed methods are based on the application of optical and electron microscopy and may be used to find the angles of contact over a wide range of particle sizes (3-10^5 nm).
Keywords: Thin films; Wetting